The impact of Tubaramure, a food-assisted integrated health and nutrition program in Burundi, on household food consumption and maternal and child dietary diversity - Leroy, Jef L.; Olney, Deanna K.; Bliznashka, Lilia; Ruel, Marie T. (Wiley, 2015)
Tubaramure is a food‐assisted integrated health and nutrition program that targets pregnant women and their child up to 2 y of age (first 1000 d) in two highly food insecure provinces in Burundi. Monthly food rations include corn‐soy‐blend (CSB) and vit A‐ and D‐fortified oil. We evaluated the program's impact using a cluster randomized controlled study, where 60 villages were assigned to one of 4 study groups who received benefits for different durations: T24: pregnancy up to 24 m; T18: pregnancy to 18 m; TNFP: same as T24, but without food rations during pregnancy; and Control. We estimated the program's impact on household energy consumption (HHEC), women's dietary diversity (WDD) and children's (6‐24 m) minimum dietary diversity (MDD), using repeated cross‐sectional data collected at baseline and again 2 y later.Compared to the control group, program beneficiaries had significantly greater HHEC (by ~ 600 kcal/d/adult equivalent), due to greater consumption of foods from the rations, and of fruits. The program had a small positive impact of ~0.3 food groups on WDD, mainly driven by a large increase in the proportion of mothers consuming legumes (~16 pp) (from CSB). The program led to a ~10 pp increase in the proportion of children fed MDD, but had no effect on the proportion consuming any one food group. Differences between treatment groups will be discussed. Our effectiveness trial showed that Tubaramure's positive effect on HH and individual diets was mostly due to the direct impact of the food rations in this severely food insecure population.Funded by USAID's Food and Nutrition Technical Assistance Project & CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), led by IFPRI.